Perlindungan Hukum Tenaga Kerja Dengan Sistem Outsourcing Di Indonesia - Wiwin Budi Pratiwi; Devi Andani (Fakultas Hukum Universitas Islam Indonesia, 2022)
The problem brought up in this research is the implementation of legal protection for outsourcing workers is still minimal, especially with the enactment of Law Number 11 of 2020 on Job Creation, which is considered to be increasingly legalizing outsourcing. The purpose of this research is to analyze the legal protection for outsourced workers in Indonesia. This is a normative juridical research which utilises statutory and conceptual approaches. The source of the research is secondary data in which the analysis was carried out in a qualitative descriptive manner. The results of the study conclude that legal protection for outsourced workers in Indonesia is regulated in Law Number 11 of 2020 on Job Creation. Law Number 11 of 2020 on Job Creation removes the provisions of Article 64 and Article 65 of Law Number 13 of 2003 on Manpower. Article 66 of the Job Creation Law does not include restrictions on jobs that are prohibited from being carried out by outsourced workers, whereas in Article 65 paragraph (2) of the Manpower Law previously it was regulated regarding jobs that could be handed over to other companies. Other provisions allow no time limit for workers which allows workers to be outsourced indefinitely or even for life. The provisions in the Employment Creation Law that protect the rights of outsourced workers are still regulated in Article 66 paragraph (5) of the Job Creation Law related to wages, welfare, working conditions, disputes that arise are the responsibility of the outsourcing company. Key Words: Outsourcing; legal protection; labor AbstrakPermasalahan dalam penelitian ini adalah masih minimnya implementasi perlindungan hukum bagi tenaga kerja outsourcing terlebih dengan diundangkannya Undang-Undang Nomor 11 Tahun 2020 tentang Cipta Kerja dianggap semakin melegalkan outsourcing. Tujuan penelitian untuk menganalisis perlindungan hukum bagi tenaga kerja outsourcing di Indonesia. Jenis penelitian adalah yuridis normatif. Metode pendekatan yang digunakan adalah pendekatan perundang-undangan dan konseptual. Sumber data yang digunakan adalah data sekunder. Analisis data dilakukan secara deskriptif kualitatif. Hasil penelitian menyimpulkan bahwa perlindungan hukum bagi tenaga kerja outsourcing di Indonesia diatur dalam Undang-Undang Nomor 11 Tahun 2020 tentang Cipta Kerja. Undang-Undang Nomor 11 Tahun 2020 tentang Cipta Kerja menghapus ketentuan Pasal 64 dan Pasal 65 Undang-Undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan. Pasal 66 UU Cipta Kerja tidak dicantumkan mengenai batasan pekerjaan yang dilarang dilaksanakan oleh pekerja outsourcing, padahal dalam Pasal 65 ayat (2) UU Ketenagakerjaan sebelumnya diatur mengenai pekerjaan yang dapat diserahkan kepada perusahaan lain. Ketentuan lain memungkinkan tidak ada batas waktu bagi pekerja yang memungkinkan pekerja dapat di outsourcing tanpa batas waktu bahkan bisa seumur hidup. Ketentuan dalam UU Cipta Kerja perlindungan hak bagi pekerja outsourcing tetap ada yang diatur dalam Pasal 66 ayat (5) UU Cipta Kerja terkait dengan upah, kesejahteraan, syarat-syarat kerja, perselisihan yang timbul menjadi tanggung jawab perusahaan outsourcing. Kata-kata Kunci: Outsourcing; perlindungan hukum; tenaga kerja